CAN DARK CHOCOLATE IMPROVE OUR COGNITIVE SKILLS? EVALUATING THE IMPACT OF COCOA FLAVANOLS ON FUNCTION OF THE BRAIN – A REVIEW ARTICLE - Wojciech Ługowski; Julia Samek; Karolina Bartoszewska; Weronika Matwiejuk; Iga Kwiecień; Jakub Komorowski-Roszkiewicz; Karol Marcyś (International Journal of Innovative Technologies in Social Science, 2025)
This review evaluates the impact of cocoa consumption, particularly flavanol-rich dark chocolate, on cognitive function based on evidence from 25 human studies. A structured literature search was conducted in the PubMed database using predefined keywords, and relevant studies were selected according to methodological quality and relevance. Cognitive domains assessed included memory, processing speed, executive function, and visual cognition. Findings from randomized controlled trials and meta-analyses indicate modest cognitive benefits, especially in long-term memory and processing speed, primarily among middle-aged and older adults following chronic flavanol intake. Functional neuroimaging studies support underlying mechanisms such as enhanced cerebral perfusion, increased neuronal efficiency, and modulation of hippocampal function. Short-term improvements were observed in episodic and spatial memory, reaction time, and visual sensitivity. However, results across studies are inconsistent. Large-scale trials, notably the COSMOS project, reported no significant cognitive benefits from daily cocoa flavanol supplementation in the general population, though limited improvements were noted in individuals with poor dietary quality. Some trials reported null or adverse outcomes, particularly in younger adults and when cocoa was combined with omega-3 fatty acids. In conclusion, cocoa flavanol intake may confer cognitive benefits in specific populations and contexts. However, variation in study design, dosing, and baseline characteristics limits generalizability. Further research is warranted to establish optimal intake regimens, identify responsive subgroups, and determine long-term safety.